(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Starting from the understanding that the dancing body is political, this article establishes relations between dance and politics from the discourses that are taken to the scene in the show Caixa de ilusões, of the Ânima companhia de dança, directed by choreographer Eva Schul.